The Relationship Between Perceived Parental Bonding and Bullying: The Mediating Role of Empathy - Effrosyni Mitsopoulou (European Journal of Counselling Psychology, 2013)
Despite the importance of parenting in the development of empathy in children as well as their involvement in bullying behaviours, no study has ever examined the mediating role of empathy in the relationship between parental bonding and bullying and victimization. The present study aims in examining these relationships. Participants included 504 children (255 boys, 246 girls) from different primary schools of Crete. The standard version of the Peer Experiences Questionnaire was used to assess experiences in bullying behaviours, the Parental Bonding Instrument was used to assess self-reported sense of care and overprotection from the mother and father separately, whereas empathy was assessed using the Greek version of Bryant’s Empathy Index. A series of multiple regression analyses were conducted. Results showed that boys scored significantly higher on average with respect to Victimisation of Others, and girls scored higher to specific sub-factors of empathy. It was also found that in the case of Care Mother, Sadness and Understanding of Feelings were significant mediators of Victimization of Others. Further, in the subsample of boys it was revealed that Sadness and Understanding of Feelings were significant mediators of the relationship between Care Mother and Victimization of Others. Implications for counselling interventions are also discussed.